Soundscapes in the German Baltic Sea Before and During the Covid-19 Pandemic - Basan, Fritjof; Fischer, Jens-Georg; Kühnel, Dennis (Frontiers in Marine Science, 2021)
Anthropogenic underwater noise has been identified as one of the main pressures on the marine environment. Considerable research efforts have been made to quantify acoustic soundscapes on different spatial and temporal scales in order to identify trends and investigate possible risks for the marine ecology. Measures to reduce the anthropogenic noise input into the seas are under discussion, including the reduction of vessel speed or re-routing of shipping lanes. The decline in maritime transport caused by the Covid-19 pandemic provides an opportunity to examine the associated extent of noise reduction. As part of an international initiative, coordinated by the International Quiet Ocean Experiment, acoustic data-sets from two measurement positions in the German Baltic Sea were investigated. Following the approach of a “Before-After Control-Impact” study the available recordings from the period before the Covid-19 pandemic, dating back to 2014, are compared to recordings from the year 2020. Monthly statistics from the period before the pandemic and from the year 2020 are compared. To account for varying natural conditions the measurements were sorted into categories of same prevailing sea state. Through this approach, measurements with equivalent natural noise impact are compared, focusing on the variability of the anthropogenic noise. A decline in sound pressure of 12 - 14 % for low frequency bands and a correspondence with decreasing marine mobility could be shown for both stations.